Influence of realistic EV fleet response with power and energy controllers in an EV-wind virtual power plant. (September 2022) - Ledro, Mirko; Calearo, Lisa; Zepter, Jan Martin; Gabderakhmanova, Tatiana; Marinelli, Mattia
Abstract: To facilitate the integration of volatile renewable energy sources (RES), electric vehicle (EV) fleets are considered valuable flexibility assets. With their storage capability, they can contribute to compensating for fluctuations and providing balancing support when integrated in a virtual power plant (VPP). This paper investigates the response of an EV fleet to wind power fluctuations by accounting for non-synchronized activation time and discrete modulation of the charging current. The influence of the EV fleet response is further investigated comparing a power-based controller with an energy-based one. Results show that a realistic EV fleet response affects the VPP output more when a power controller is considered. A discrete modulation of the EV charging current can cause oscillations, which would not occur with a linear modulation. Positively, the influence of a non-synchronized EV activation time is negligible for both controllers, proving that a synchronized activation time can be assumed during similar studies. Despite the equality from a mathematical perspective, the hourly VPP energy production when an EV fleet is controlled with a power controller does not correspond to when an energy controller is adopted. Highlights: Modelling of pseudo-real EV fleet response based on charging equipment. Power smoothing and energy management in EV-wind virtual power plant. EV smart charging under chargers standards and users' behaviour. EV charging modulation affects the wind farm output more than EV activation time.